2018
DOI: 10.1182/blood-2018-99-114346
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Long-Lasting Anti-CD19 Activity of Engrafted CD19 Chimeric Antigen Receptor Modified T Cells in a Phase I Study Targeting Pediatrics with Acute Lymphoblastic Leukemia

Abstract: Introduction: 90% of relapse/refractory B cell acute lymphatic leukemia (R/R B-ALL) patients can achieve complete remission (CR) after CD19-targeting chimeric antigen receptor T (CAR-T) cell therapy. However, around 50% of them relapse in one year. Persistent CAR-T cell engraftment is considered as the key to remain durable remission. Here we initiated a Phase I study to treat pediatric B-ALL patients using CD19 CAR-T cell. After treatment, CD19+ minimal residual disease (MRD) and CAR-T engraftment were detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…In our study, in order to increase the target specificity and reduce immune escape, we adopted a tandem structure in design of CAR molecule for two antigenic targets using second-generation CAR-T conception. The results indicated that both two CARs showed antitumor activity rather than interacting with each other, which may be attributed to the hinge domain supplying space for scFv folding [29][30][31]. MUC16 and PDL1 are undoubtedly ideal target antigens for CAR-T technology against OC in our study.…”
Section: Discussionmentioning
confidence: 78%
“…In our study, in order to increase the target specificity and reduce immune escape, we adopted a tandem structure in design of CAR molecule for two antigenic targets using second-generation CAR-T conception. The results indicated that both two CARs showed antitumor activity rather than interacting with each other, which may be attributed to the hinge domain supplying space for scFv folding [29][30][31]. MUC16 and PDL1 are undoubtedly ideal target antigens for CAR-T technology against OC in our study.…”
Section: Discussionmentioning
confidence: 78%
“…It is worth noting that the added value of CAR‐T therapy might yet to be fully justified, 8 as only few studies have been published with long‐term follow‐up, which indicate effectiveness but are single arm, Phase 1 or 2 trials 47‐50 . Several studies have provided some evidence of CAR‐T being cost‐effective compared to the existing therapies at higher thresholds, 36,37,51 although it should be noted that its comparators were of high price as well 3,51,52 …”
Section: Discussionmentioning
confidence: 99%
“…41 Against this background, more recently developed "in-house" It is worth noting that the added value of CAR-T therapy might yet to be fully justified, 8 as only few studies have been published with long-term follow-up, which indicate effectiveness but are single arm, Phase 1 or 2 trials. [47][48][49][50] Several studies have provided some evidence of CAR-T being cost-effective compared to the existing therapies at higher thresholds, 36,37,51 although it should be noted that its comparators were of high price as well. 3,51,52 Although a novel, promising therapy, the centralized production paradigm of CAR-T cells in a commercial setting is less than satisfactory, particularly in light of its high price tag.…”
Section: Acquisition Costsmentioning
confidence: 99%
“…immunotherapy (14)(15)(16)(17)(18)(19). Although CAR T-cell therapy has been recognized by major cancer medical centers, it still has serious side effects and toxicity, which can rapidly lead to fatal cytokine-release syndrome (CRS) (20,21) and neurotoxicity [CAR T cell-related encephalopathy syndrome (CRES)] (22).…”
Section: Cluster Of Differentiation 19 Chimeric Antigen Receptor T-cementioning
confidence: 99%
“…Although CAR T-cell therapy has been recognized by major cancer medical centers, it still has serious side effects and toxicity, which can rapidly lead to fatal cytokine-release syndrome (CRS) (20,21) and neurotoxicity [CAR T cell-related encephalopathy syndrome (CRES)] (22). Long-term side effects include a risk of chronic B-cell deficiency (14). Hence, in the present review, the research progress and improvements in CAR T-cell treatment for ALL in children are assessed, and the relapse-related experiences and future prospects are analyzed.…”
Section: Cluster Of Differentiation 19 Chimeric Antigen Receptor T-cementioning
confidence: 99%